2021
DOI: 10.3390/mi12040431
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic Mixing of Non-Newtonian Fluid in a Microchannel with Obstacles and Zeta Potential Heterogeneity

Abstract: This paper investigates the electroosmotic micromixing of non-Newtonian fluid in a microchannel with wall-mounted obstacles and surface potential heterogeneity on the obstacle surface. In the numerical simulation, the full model consisting of the Navier–Stokes equations and the Poisson–Nernst–Plank equations are solved for the electroosmotic fluid field, ion transport, and electric field, and the power law model is used to characterize the rheological behavior of the aqueous solution. The mixing performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Both arrangements show similar improvement in mixing efficiency; however, the asymmetric configuration of the surface potential shows a higher flow rate. Mei et al [24] investigated how zeta potential heterogeneity and obstruction affects the non-Newtonian fluid's mixing characteristics. They found that mixing efficiency improved as obstacle height and zeta potential increased.…”
Section: Introductionmentioning
confidence: 99%
“…Both arrangements show similar improvement in mixing efficiency; however, the asymmetric configuration of the surface potential shows a higher flow rate. Mei et al [24] investigated how zeta potential heterogeneity and obstruction affects the non-Newtonian fluid's mixing characteristics. They found that mixing efficiency improved as obstacle height and zeta potential increased.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that elasticity did not significantly change the flow of polyvinyl pyrrolidone and polyethylene oxide dilute non-Newtonian solutions (in comparison with Newtonian solution). Mei et al (2021) investigated the EO micro-mixing through a microchannel with obstacles on the wall. Their results showed that by increasing the zeta potential of the obstacle surface, mixing efficiency would be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The wal zeta-potential is considered negative for the heterogeneity segment, so there is positiv zeta-potential everywhere except for the heterogeneity patch. Microchannels can be designed through proper heterogeneity arrangement on channel surfaces for mixing, pumping, or both [27,28]. Under such a circumstance, th numerical solution of electroosmotic flow in heterogeneous channels without using th Helmholtz-Smoluchowski (H-S) approximate model is time-consuming [29,30], and few studies have been done in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The surface-to-volume ratio is high in microchannels due to the small length scale so surface phenomena, useless in large-scale flows, are crucial in such microfluidic de vices. One of these surface phenomena playing an essential role in microfluidics is th Microchannels can be designed through proper heterogeneity arrangement on channel surfaces for mixing, pumping, or both [27,28]. Under such a circumstance, the numerical solution of electroosmotic flow in heterogeneous channels without using the Helmholtz-Smoluchowski (H-S) approximate model is time-consuming [29,30], and few studies have been done in this field.…”
Section: Introductionmentioning
confidence: 99%